The accuracy of the cheating detection methods in large-scale tests: mathematics national examination - Nulangi, Thomas Mbenu; Mardapi, Djemari (Jurnal Penelitian dan Evaluasi Pendidikan, 2018)
This study aimed to describe (1) the characteristics of items based on the Item Response Theory, (2) the cheating level in the implementation of the national examinartion based on Angoffs B-Index method, Pair 1 method, Pair 2 method, Modified Error Similarity Analysis (MESA) method, and G2 method, (3) the most accurate method to detect the cheating in the mathematics national examination at the senior secondary school level in the academic year of 2015/2016 in East Nusa Tenggara Province. The result of the item response theory analysis showed that 17 (42.5%) items of the mathematics national examination fit with the 3-PL model, with the maximum information function of 58.0128 at 1.6, and the measurement error of 0.1313. The number of pairs detected to be cheating by Angoff's B-Index method was 63 pairs, that by the Pair 1 method was 52 pairs, that by the Pair 2 method was 141 pairs, that by MESA method was 67 pairs, and that by the G2 method was 183 pairs. The methods which could detect most pairs doing cheating were the G2 method, the Pair 2 method, the MESA method, Angoff's B-Index method, and the Pair 1 method successively. The methods which could accurately detect cheating based on the computation of the standard error were Angoff's B-Index method, the G2 method, the MESA method, the Pair 1 method, and the Pair 2 method successively.